Initiation of breastfeeding and prevalence of exclusive breastfeeding at hospital discharge in urban, suburban and rural areas of Zhejiang China - Qiu, Liqian; Zhao, Yun; Binns, Colin; Lee, Andy; Xie, X. (BioMed Central, 2009)
Background: Rates of exclusive breastfeeding in China are relatively low and below national targets. The aim of this study was to document the factors that influence exclusive breastfeeding initiation in Zhejiang, PR China. Methods: A cohort study of infant feeding practices was undertaken in Zhejiang Province, an eastern coastal region of China. A total of 1520 mothers who delivered in four hospitals located in city, suburb and rural areas during late 2004 to 2005 were enrolled in the study. Multivariate logistic regression analysis was used to explore factors related to exclusive breastfeeding initiation. Results: On discharge from hospital, 50.3% of the mothers were exclusively breastfeeding their infants out of 96.9% of the mothers who had earlier initiated breastfeeding. Exclusive breastfeeding was positively related to vaginal birth, baby's first feed being breast milk, mother living in the suburbs or rural areas, younger age of mother, lower maternal education level and family income. Conclusion: The exclusive breastfeeding rate in Zhejiang is only 50.3% on discharge and does not reach Chinese or international targets. A number of behaviours have been identified in the study that could be potentially incorporated into health promotion activities.